Quality of work life of librarians in government academic libraries in the Klang Valley - Abdul aziz, Rafidah; Mohd Nadzar, Fuziah; Husaini, Haslinda; Maarof, Asmah; Mohd Radzi, Salleh; Ismail, Izhairi (Elsevier, 2011)
The success of any organization is highly dependent on how it attracts workers and motivates, and retains its workforce. Today’s organizations need to be more flexible and understanding,so that they are well prepared to develop their employees and enjoy their commitment. The purpose of this study was to investigate the relationship between work and non-work variables and quality of work life. It is anticipated that the contribution from this study will provide useful information to the top management level in organizations for the purpose of planning appropriate policies that can enhance employees’ overall life satisfaction. The research questions, which serve as a foundation of this study, focus on the relationship between work and non-work variables and quality ofwork life. This study applied a quantitative research design aswell as descriptive and correlation approach. Respondents are all librarians working in government academic libraries in the Klang Valley, Malaysia. An online survey was used to gather data for each participating library. The questionnaire was divided into two sections: Section A, the socio-demographic information; and Section B, the seven questions related to the study. The data were analyzed using Pearson Correlation Analysis. Findings from this study indicated that both work variables and non-work variables do matter in determining the quality of work life. The findings of this research also can be beneficial in Human Resource Management issues and trends in libraries administration.